القتل الرحيم دراسة مقارنة بين القانون الوضعي والتشريع الإلهي: Euthanasia: A Comparative Study between Positive Law and Divine Legislation - al Atrash, Esam Husni (Jurnal Fiqh, 2023)
This study aimed to identify the provisions of euthanasia in positive law and divine legislation, and also aimed to identify the provisions of positive or negative euthanasia, both legally and religiously, the study used the analytical method, and the comparative method, The study reached a number of results, most notably, the convergence of comparative legislation on euthanasia, some of which permitted it, especially Western legislation, and some of it criminalized, especially Islamic legislation. Whether positive or negative, they considered it a crime of intentional killing, just as the three monotheistic religions unanimously agreed on the prohibition of euthanasia and considered it a crime of unlawfully killing a human being, The jurists unanimously agreed on the prohibition of positive euthanasia, just as the jurists differed on the prohibition of passive euthanasia.